Alternatif Penggunaan Sulfit Dalam Pembuatan Chips Umbi Porang (Amorphophallus oncophyllus) Sebagai Peningkatan Nilai Derajat Putih - Amyranti, Mutia; Maftukhah, Siti (UNIVERSITAS ISLAM SYEKH - YUSUF TANGERANG, 2021)
discoloration is the result of the action of endogenous polyphenol oxidase (enzymatic browning) followed by spontaneous polymerization of quinonoid compounds with other food components. Currently, the use of sulfite agents is the most widely used chemical approach to control browning of foods. However, consumer awareness of the risks associated with sulfites and growing regulations make sulfites an alternative. Efforts should be made to reduce the degree of browning of porang tuber chips caused by enzymatic non-enzymatic browning. The purpose of this study was to study the alternative use of sulfite as an anti-browning agent against the whiteness value of porang tuber chips. The alternative type of sulfite used is ascorbic acid. Ascorbic acid concentration (2, 5 and 7.5%) and immersion time (30, 60, 90, 120, 150 and 180 minutes) were selected as independent variables. The best condition for preventing browning of porang tuber chips was obtained by using 5% ascorbic acid at a time of soaking for 180 minutes and obtained the highest whiteness value (79.41). Keywords: anti-browning agents, lightness, chips porang